2012
DOI: 10.1111/j.1469-7580.2012.01526.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the mammalian middle ear and jaw: adaptations and novel structures

Abstract: Having three ossicles in the middle ear is one of the defining features of mammals. All reptiles and birds have only one middle ear ossicle, the stapes or columella. How these two additional ossicles came to reside and function in the middle ear of mammals has been studied for the last 200 years and represents one of the classic example of how structures can change during evolution to function in new and novel ways. From fossil data, comparative anatomy and developmental biology it is now clear that the two ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
154
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(163 citation statements)
references
References 73 publications
5
154
1
2
Order By: Relevance
“…Recent developmental biology and classical paleology concur with the opinion that the malleus and incus within the mammalian tympanic cavity are homologous to the articulating part of the lower and upper jaws (quadrate and articular bone) of the jaw joint in non-mammalian jawed vertebrates (the articulo-quadrate joint) [12]. This joint remains in mammals as the incudomalleolar joint at the tympanic cavity, but lacking masticatory function.…”
Section: Phylogenic Basis Of the Jaw Joint In Non-mammals And Mammalsmentioning
confidence: 52%
See 1 more Smart Citation
“…Recent developmental biology and classical paleology concur with the opinion that the malleus and incus within the mammalian tympanic cavity are homologous to the articulating part of the lower and upper jaws (quadrate and articular bone) of the jaw joint in non-mammalian jawed vertebrates (the articulo-quadrate joint) [12]. This joint remains in mammals as the incudomalleolar joint at the tympanic cavity, but lacking masticatory function.…”
Section: Phylogenic Basis Of the Jaw Joint In Non-mammals And Mammalsmentioning
confidence: 52%
“…Mastication and sound transduction both involve the malleus and incus in non-mammalian jawed vertebrates, and an anatomical connection between these two functional apparatuses can be observed in developing mammals [8][9][10][11][12]. Additionally, the masticatory and auditory muscles seem to be intimate in nervous distribution and function in mammals.…”
Section: Introductionmentioning
confidence: 99%
“…In the primitive vertebrates and reptiles, the columella derived from the second gill arch (Kӧppl et al, 2013). Reptiles and birds have one ossicle, homologous to the mammalian stapes (O'Gorman, 2005;Chapman, 2011;Anthwal et al, 2013). The stapedial anlage of human consists of a mesenchymal condensation (Rodríguez-Vázquez, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In a fascinating evolutionary story, the middle ear bones of mammals have their origins in the bones that form the jaw and connect the viscerocranium to the ear in fish (Fig. 2A; reviewed by Anthwal, Joshi, & Tucker, 2012; Gould, 1990). Anatomical, developmental, and evolutionary analyses have confirmed that the posterior end of Meckel’s cartilage and part of the palatoquadrate are evolutionarily homologous to the first arch-derived malleus and incus of the mammalian middle ear, with the second arch-derived hyomandibula representing the stapes homolog (Fig.…”
Section: Zebrafish Craniofacial Anatomymentioning
confidence: 99%